The use of fluorescent light in the microbiological diagnosis of chronic wounds, using the example of pressure ulcers - Mościcka, Paulina; Cwajda-Białasik, Justyna; Filipska-Blejder, Karolina; Szewczyk, Maria T. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2025)
A significant bacterial burden in the pressure ulcer (PUs) wound bed plays a major role in delayed tissue healing. Fluorescent light is used to stain tissues inhabited by pathogens, depending on the type of microorganism: red for Staphylococcus aureus, Escherichia coli , and others, and cyan for Pseudomonas aeruginosa . The aim of our study was to describe the use of fluorescent light in the microbiological diagnosis of PUs. We present a fluorescent method of fluorescent imaging and 2 case reports of patients with PUs. In both cases, material for microbiological examination was collected using a swab. We have proven that fluorescent imaging is an effective method of microbiological diagnostics of PUs. The use of fluorescent light allows for the rapid implementation of targeted actions and acceleration of the healing process.